2017
DOI: 10.1111/acem.13120
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Telemedicine Is Used for More Severely Injured Rural Trauma Patients, but Does Not Decrease Transfer: A Cohort Study

Abstract: Emergency department-based telemedicine consultation is requested for the most severely injured rural trauma patients, especially with those with penetrating trauma, burns, and abnormal presenting vital signs. Telemedicine consultation was not independently associated with increased probability of transfer. Future work should evaluate how telemedicine impacts the timeliness of care and specific care interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…The overall purpose of conducting this analysis was to identify areas where novel delivery of specialty care might avoid the need for some VHA transfers. In civilian health systems, ED-based telemedicine has been used to provide specialty provider and nursing support with the goal of improving transfer appropriateness [23][24][25][26][27][28][29][30][31]. This service has been most broadly implemented in telestroke care, providing real-time video consultation by a neurologist to an ED for the purpose of selecting patients for intravenous thrombolysis [32].…”
Section: Discussionmentioning
confidence: 99%
“…The overall purpose of conducting this analysis was to identify areas where novel delivery of specialty care might avoid the need for some VHA transfers. In civilian health systems, ED-based telemedicine has been used to provide specialty provider and nursing support with the goal of improving transfer appropriateness [23][24][25][26][27][28][29][30][31]. This service has been most broadly implemented in telestroke care, providing real-time video consultation by a neurologist to an ED for the purpose of selecting patients for intravenous thrombolysis [32].…”
Section: Discussionmentioning
confidence: 99%
“…The USA has seen a dramatic expansion in telehealth programme driven by the critical need to provide high-quality care while reducing healthcare costs 1–24. To date, most acute care telehealth activity has focused on Telestroke1 2; however, Emergency Medicine (EM) is a specialty uniquely positioned to directly impact patient movement and system utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have discussed the role of telemedicine in avoiding unnecessary transfers across different settings [33, 43-46, 48, 100]. Others found that telemedicine is not independently associated with probability of transfer [61,98]. While some studies showed evidence of increased transfer rates in competitive tertiary care environments associated with telemedicine implementation [101].…”
Section: Discussionmentioning
confidence: 99%
“…Research Center at the University of Iowa. These centers were involved in several studies that explored the quality of care in CAHs [20][21][22][55][56][57] and designed comparative effectiveness studies to test multiple hypotheses related to quality and timeliness of care in rural hospitals using telemedicine [33,[58][59][60][61].…”
Section: Gaps In Existing Knowledgementioning
confidence: 99%